2019
DOI: 10.1016/j.ijcard.2019.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Large variability in clinical judgement and definitions of left bundle branch block to identify candidates for cardiac resynchronisation therapy

Abstract: Background: Left bundle branch block (LBBB) morphology is associated with improved outcome of cardiac resynchronisation therapy (CRT) and is an important criterion for patient selection. There are, however, multiple definitions for LBBB. Moreover, applying these definitions seems subjective. We investigated the inter-and intraobserver agreement in the determination of LBBB using available definitions, and clinicians' judgement of LBBB. Methods: Observers were provided with 12-lead ECGs of 100 randomly selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 18 publications
0
27
0
2
Order By: Relevance
“…As a matter of fact, these patients may benefit from CRT instead . Third, as reported by van Stipdonk et al, different definitions (ESC, AHA/ACC/HRS, MADIT, and Strauss) have significant variation in the probability of classifying LBBB. As a result, it is better to compare all of these definitions for the impact of successful LBBAP.…”
Section: Discussionmentioning
confidence: 89%
“…As a matter of fact, these patients may benefit from CRT instead . Third, as reported by van Stipdonk et al, different definitions (ESC, AHA/ACC/HRS, MADIT, and Strauss) have significant variation in the probability of classifying LBBB. As a result, it is better to compare all of these definitions for the impact of successful LBBAP.…”
Section: Discussionmentioning
confidence: 89%
“…The cut-off of 150 ms is based on subgroup analyses of large CRT trials which demonstrated that positive outcome of CRT was predominantly confined to patients with a QRS duration !150 ms [20]. While classifying LBBB may seem trivial for cardiologists, considerable intra-and inter-observer variability exists in whether a patient has LBBB or not [21]. There exist multiple criteria for diagnosis of LBBB and the strength of the association of LBBB to outcome in CRT depends on its classification [22].…”
Section: Traditional Determinants Of Crt Responsementioning
confidence: 99%
“…Their HFQRS maps express a rather RBBB pattern, and special attention should be paid to the biventricular stimulator settings if ever implanted. The proper setting of cut-off values (QRSd, definitions of notches and slurs), as well as the debate about the best definition of SLBBB based on QRS shape, remains wide open [17, 18, 19, 20]. SLBBB classification is a binary parameter defined from multiple binary sub-parameters such as QRSd and the occurrence of notches and slurs.…”
Section: Discussionmentioning
confidence: 99%